Carbon supports for the oxidative cleavage of oleic acid: Influence of textural properties - Gámez, Sebastián; de la Torre, Ernesto; Gaigneaux, Eric M. (Molecular catalysis, 2022)
•Ru-carbon catalysts active and selective for the oxidative cleavage of oleic acid.•Macroporous carbon black provides high conversion (>99%) and yields (∼75%).•CBO-Ru(2%) maintains its activity up to 3 recycling tests.•Microporous materials not suitable for the oxidative cleavage of large alkenes. Microporous oxidized activated carbon (ACO) and macroporous oxidized carbon black (CBO) were assessed in the complexation of Ru for the oxidative cleavage of oleic acid. This reaction breaks carbon-carbon double bond to produce azelaic and pelargonic acids (highly demanded in pharmacology). Both carbon materials were treated with HNO3 prior Ru deposition by wet impregnation method. Carbon supports were characterized by FTIR, Boehm's titration and N2 physisorption, while Ru complexation was determined by ICP and XPS spectroscopy. Activated carbon catalyst displayed a low conversion (∼53%) in comparison to carbon black catalyst (>99%). The reason is related to the molecular length of oleic acid (2.2 nm), estimated by ab initio Hartree-Fock calculation, which is larger than micropores from activated carbon (∼0.7 nm). Despite Ru losses during the catalytic tests, CBO was more active and stable than ACO, confirming that a macroporous support is more suitable to perform the oxidative cleavage of oleic acid. [Display omitted]